Pengaruh Return On Assets dan Ukuran Perusahaan Terhadap Struktur Modal PT.Mayora Indah Tbk - Rahkutin Rahkutin; Alwi Alwi (CAPITAL: Jurnal Ekonomi dan Manajemen, 2020)
This study aims to (1) study and analyze the effect of Return On Assets on capital structure at PT.Mayora Indah Tbk, (2) study and analyze the influence of company size on capital structure at PT.Mayoran Indah Tbk, (3) find and analyze the influence Return On Assets and Company Size on the capital structure at PT.Mayora Indah Tbk. The population used in this study is PT.Mayora Indah Tbk's financial statements published on the Stock Exchange. The sampling technique used is the purposive sampling method. Data analysis techniques used are (1) classic assumption test (2) multiple linear regression, (3) multiple coordination coefficients, (4) coefficient of determination, (5) t test and f test. The results of the study indicate that the Return On Assets are partially partial to the capital structure, while the size of the company does not conflict partially with the capital structure, (f test) shows that there is a significant influence between the Return on Assets and the size of the company on the capital structure.